For home and country : a Civil War scrapbook - Bolotin, Norm, 1951-; Herb, Angela M. (New York : Lodestar Books/Dutton, 1995)
A brief account of the Civil War liberally illustrated with photographs of the period and excerpts from personal letters and newspapers.
Introduction : war fever -- Citizen to soldier -- Outfitting the troops -- The rigors of war -- Making do -- Feast or famine -- A path of destruction -- A world of death -- The sick and wounded -- Prisoners of war -- Writing home -- News of the war -- Photographing the war -- Battling boredom -- Marching home.
"6th book in unnumbered series"--CIP info.
Includes bibliographical references.
Book Links (A.L.A.)
Child Study Children's Book Committee
Publisher's Weekly
7.7
Keywords: United States -- History -- Civil War, 1861-1865 -- Pictorial works -- Juvenile literature; United States -- History -- Civil War, 1861-1865 -- Juvenile literature; United States -- History -- Civil War, 1861-1865.; United States -- History -- 1861-1865, Civil War -- Pictorial works; United States -- History -- 1861-1865, Civil War